2013
DOI: 10.1212/wnl.0b013e31827b1a1c
|View full text |Cite
|
Sign up to set email alerts
|

Active MS is associated with accelerated retinal ganglion cell/inner plexiform layer thinning

Abstract: Objective: To determine the effect of clinical and radiologic disease activity on the rate of thinning of the ganglion cell/inner plexiform (GCIP) layer and the retinal nerve fiber layer in patients with multiple sclerosis (MS) using optical coherence tomography (OCT).Methods: One hundred sixty-four patients with MS and 59 healthy controls underwent spectraldomain OCT scans every 6 months for a mean follow-up period of 21.1 months. Baseline and annual contrast-enhanced brain MRIs were performed. Patients who d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
156
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 199 publications
(174 citation statements)
references
References 36 publications
14
156
2
2
Order By: Relevance
“…Our findings expand on prior studies that demonstrated that retinal layers (pRNFL and GCL 1 IPL) reflect global clinical and radiologic CNS processes in MS, and that specific retinal layers may reflect differential pathologic processes, including neurodegeneration and inflammation. 27,29 Our findings suggest that not only do retinal and SC-MRI measures reflect global pathologic processes in MS that are not adequately captured by brain atrophy alone, but that the regional and global pathologic processes that SC-MRI reflect are distinct from those that are captured by retinal measures, and that these processes independently contribute to mediating clinical disability in various functional systems. These findings highlight the importance of including an assessment of multiple compartments of the CNS affected by MS to better understand both global and regional disease processes, their interplay, and how they contribute to clinical disability in various functional systems.…”
Section: Resultsmentioning
confidence: 85%
“…Our findings expand on prior studies that demonstrated that retinal layers (pRNFL and GCL 1 IPL) reflect global clinical and radiologic CNS processes in MS, and that specific retinal layers may reflect differential pathologic processes, including neurodegeneration and inflammation. 27,29 Our findings suggest that not only do retinal and SC-MRI measures reflect global pathologic processes in MS that are not adequately captured by brain atrophy alone, but that the regional and global pathologic processes that SC-MRI reflect are distinct from those that are captured by retinal measures, and that these processes independently contribute to mediating clinical disability in various functional systems. These findings highlight the importance of including an assessment of multiple compartments of the CNS affected by MS to better understand both global and regional disease processes, their interplay, and how they contribute to clinical disability in various functional systems.…”
Section: Resultsmentioning
confidence: 85%
“…Prior studies demonstrate that OCT-derived ganglion cell 1 inner plexiform layer (GCIP) thickness has superior reliability and reproducibility and correlates better with visual function and disability in MS than peripapillary retinal nerve fiber layer thickness (pRNFL). [8][9][10] Rates of GCIP thinning are accelerated in patients with MS exhibiting inflammatory activity, 11 and correlate strongly with rates of brain, particularly gray matter, atrophy over time. 8 Despite the increasing support for OCT as an outcome for assessing neurodegeneration in MS trials, whether different DMTs differentially affect retinal atrophy in MS remains to be assessed.…”
mentioning
confidence: 99%
“…by iNOS has deleterious effects on the electron transport chain, and is a major cause of neuronal and axonal damage [14]. The pro-inflammatory cytokine TNF-a is a key component of the signaling cascade associated with the inflammatory response in nervous tissue resulting in cellular damage [29].…”
Section: Discussionmentioning
confidence: 99%